Mapping of sequences with 2-fold symmetry on the simian virus 40 genome: a photochemical crosslinking approach. - Shen, C K (1977)
Sequences with 2-fold axes of symmetry have been detected and mapped on the simian virus 40 (SV40) genome by their ability to form hairpin turns in single-stranded SV40 DNA. Supercoiled SV40 DNA (SV40 I) was digested with restriction enzymes EcoRI and HpaII. The resulting linear DNA molecules with lengths of the complete SV40 genome were then denatured and photochemically reacted with 4,5',8-trimethylpsoralen (trioxsalen) at 16.0 +/- 0.5 degrees and different ionic strengths. Secondary structures on the single-stranded SV40 DNA were crosslinked and their positions analyzed by electron microscopy. There were no observable hairpin turns on the denatured SV40 DNA when it was photoreacted in 1 mM Tris-HCl/0.1 mM EDTA at pH 7.0. In 20 mM NaCl, one specific hairpin turn was detected at 0.17 +/- 0.02 map units on the map of EcoRI-digested SV40 DNA, where the 3' ends of early 19S mRNA, late 19S mRNA, and 16S mRNA of SV40 have been mapped. In 30 mM NaCl there are five more major hairpin turns besides the most stable one. The centers of four of these specific hairpin turns were mapped at 0.26 +/- 0.02, 0.68 +/- 0.03, 0.84 +/- 0.02, and 0.94 +/- 0.01 units on the map of EcoRI-digested SV40. The fifth one is at or near the unique EcoRI cleavage site on SV40 DNA. The possible functions of these sequences are discussed in terms of the nature of the promoter sites, the replication origin, the processing of RNA precursors, and regulation at the translational level.